Pete the cat and the new guy eaudiobook - Dean, James (Pete the Cat., 2014)
From Kimberly and James Dean's bestselling Pete the Cat series comes a groovy story about new beginnings and new friends. There's a new guy in town, and Pete can't wait to meet him. After all, more friends mean more fun. When Pete finally meets Gus, he realizes they're very different from each other...and that's what makes him cool. So when Gus starts to doubt himself, it's up to Pete to convince him that there's something everyone can do. Gus is special in his own way, just like Pete and just like you! The message of accepting others and yourself shines through and is perfect for young readers learning to navigate friendship issues. Fans of Pete the Cat will delight in the rhythmic storytelling and fun repetition throughout the book. The fun never stops—download the free groovin' song! Don't miss Pete's other adventures, including Pete the Cat: I Love My White Shoes, Pete the Cat: Rocking in My School Shoes, Pete the Cat and His Four Groovy Buttons, Pete the Cat Saves Christmas, Pete the Cat and His Magic Sunglasses, Pete the Cat and the Bedtime Blues, Pete the Cat and the Cool Cat Boogie, Pete the Cat and the Missing Cupcakes, Pete the Cat and the Perfect Pizza Party, and Pete the Cat: Crayons Rock!